ANALISIS PERBANDINGAN KINERJA BANK ASING DAN BANK NASIONAL DENGAN MENGGUNAKAN RASIO KEUANGAN - Astuti, Hikmah Dwi (Jurnal Manajemen Magister Darmajaya, 2015)
Assessment on performance of a bank is conduct by analyzing the financial statement. Bank financial statement, as balance, can give information to extern party. The information is about description of financial position, that in further can be used by the extern party to estimate the risk of a bank. In perspective of ownership, there are two groups of bank, national bank and foreign bank. Both of these groups have a tight competition in order to indicate a good performance in public eyes. This research aims to analyze financial performance of national bank and foreign bank in period of 2010-2013 using financial ratio. Population of this research is national bank and foreign bank recorded in Indonesian Bank Report of 2010-2013. The samples of this research are 30 national banks and 10 foreign banks. This research uses secondary data collecting of Banking Financial Statement from www.bi.go.id to count variables used in this research. Analysis technique used in this research is Mann-Whitney test. Mann-Whitney test is used to determine different responds of 2 data populations. This test is strongest test of non-parametric tests. The analysis shows that there is a significant difference of each financial ratio of national bank and foreign bank. National bank is better in BOPO. While foreign bank is better in CAR, LDR, & ROA.Keywords: CAR, LDR, BOPO & ROA